THE RELATIONSHIP BETWEEN STRATEGIC LEADERSHIP, ORGANIZATIONAL AGILITY, AND BUSINESS PERFORMANCE IN A COMPETITIVE MARKET - Kurniawati, Fitri; Saputra, Wiwin; Novitasari, Deltari; Riyanto, Agus (Lembaga Intelektual Muda (LIM) Maluku, 2025)
In an increasingly competitive business environment, organizations must adopt strategic leadership and develop organizational agility to enhance performance. This study examines the relationship between strategic leadership, organizational agility, and business performance, exploring the mediating role of agility. Using a quantitative research approach, data was collected from business organizations across multiple industries. The findings indicate that strategic leadership significantly enhances organizational agility, which, in turn, positively impacts business performance. Furthermore, the study confirms that organizational agility mediates the relationship between strategic leadership and business performance, highlighting the importance of adaptability in sustaining competitive advantage. These insights provide valuable implications for business leaders and policymakers, emphasizing the need for fostering strong leadership and an agile organizational culture to navigate market uncertainties effectively. Future research should explore industry-specific variations and longitudinal effects to deepen the understanding of these dynamics.